The Education Meaning of Cockfighting Cartoons in Nusa Bali Newspapers - Wibawa, Arya Pageh; Swandi, I Wayan; Artha, I Gede Agus Indram Bayu (JOMANTARA, 2024)
The purpose of the publication of this article is to reveal the educational meaning of the cockfighting cartoon in the Nusa Bali newspaper. Usually, the Nusa Bali Cartoon raises public or political issues with satire, jokes, or humor. In contrast to the Nusa Bali cartoon with an education theme, it features cockfighting, which only contains satire on public issues. Problems that arise: 1) What is the meaning of the cockfighting cartoon in the Nusa Bali on June 5, 2021 ?; 2) Is the cockfighting cartoon in the Nusa Bali newspaper dated June 5, 2021, educational? The problem of this article has been solved by using a qualitative method. Primary data was collected through newspaper observations and interviews with informants. Secondary data was obtained by applying a literature study. All qualitative data was analyzed using a semiotic approach with the help of symbol theory and deconstruction theory. The results showed that: 1) The connotative and denotative meanings of the Nusa Bali cockfighting cartoon; 2) The Nusa Bali cockfighting myth depicts the chances of success without work. The educational meaning of the Nusa Bali cartoon is represented by an explanation of the disadvantages of cockfighting, the state's prohibition on gambling for Indonesian citizens, and the prohibition on Hindu scriptures and literacy for Hindus.